2011
DOI: 10.1016/s0140-6736(11)60877-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevention transformed: the new prevention research agenda

Abstract: SUMMARY We have entered a new era in HIV prevention whereby priorities have expanded from biomedical discovery to include implementation, effectiveness, and the effect of combination prevention at the population level. However, gaps in knowledge and implementation challenges remain. In this Review we analyse trends in the rapidly changing landscape of HIV prevention, and chart a new path for HIV prevention research that focuses on the implementation of effective and efficient combination prevention strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
197
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(201 citation statements)
references
References 97 publications
1
197
0
3
Order By: Relevance
“…2 Effective PMTCT programmes require women and their infants to receive a cascade of interventions including uptake of antenatal services, HIV testing during pregnancy, use of antiretroviral treatment by pregnant women living with HIV, safe child birth practices and appropriate infant feeding, uptake of infant HIV testing and other post-natal healthcare services. 3 WHO identified 22 priority countries with the top ten including India accounting for 75% of the global PMTCT services need. It was estimated that the effective scaling up of PMTCT interventions in these countries would prevent over 250,000 new infections annually.…”
Section: Introductionmentioning
confidence: 99%
“…2 Effective PMTCT programmes require women and their infants to receive a cascade of interventions including uptake of antenatal services, HIV testing during pregnancy, use of antiretroviral treatment by pregnant women living with HIV, safe child birth practices and appropriate infant feeding, uptake of infant HIV testing and other post-natal healthcare services. 3 WHO identified 22 priority countries with the top ten including India accounting for 75% of the global PMTCT services need. It was estimated that the effective scaling up of PMTCT interventions in these countries would prevent over 250,000 new infections annually.…”
Section: Introductionmentioning
confidence: 99%
“…With an intensifying imperative for a shift in global health governance for HIV/AIDS, a number of initiatives have been developed in the last decade to investigate the promise of HIV prevention -that is, to reduce individual HIV transmission and societal HIV incidence (Auerbach et al, 2011;Padian et al, 2011). Operating at both the individual and population level, prevention engages with policy-as described below and delineated in Table 1-through a combination of behavioral, structural and biomedical approaches, including:…”
Section: The Prevention Imperativementioning
confidence: 99%
“…A mathematical modeling analysis showed that the implementation of combined strategies such as medical male circumcision, earlier ART and PrEP could lead to dramatic declines in HIV-1 incidence, but will not stop transmission completely. 9 A preventive HIV-1 vaccine as part of a comprehensive prevention package 10 remains therefore among the best hopes for controlling the HIV/AIDS pandemic.…”
Section: Introductionmentioning
confidence: 99%